Biorestauration of Swage Polluted by Waste Motor Oil with Pleurotus Florida Crude Extract and Mineral Solution (Global Journal of Science Frontier Research, 2023)
In México, swage is likely contaminated by waste motor oil (WMO) that contains aliphatic and aromatic hydrocarbons. An ecological alternative to solve this problem is bio stimulation with indigenous microbiota to eliminate the aliphatic fraction of WMO. However, this aromatic part of WMO contain benzene recalcitrant, an unexplored alternative is bio stimulation with extract of Pleurotusflorida (ePf) and mineral solution for its elimination. The objetive of this research were to analyze bio stimulation swage polluted by WMO containing benzene with ePf and mineral solution for its elimination. The effect of bio stimulation of ePf plus mineral solution on the WMO and benzene was measuring by the amount of CO 2 produced. This result indicated that bio stimulation of swage polluted by WMO with Pf and mineral solution eliminated this fraction to allow the reuse of this water.
Keywords: bioremediation; laccase; water reuse; native heterotrophic microorganisms